Uji Daya Hambat Ekstrak Etanol Batang Tumbuhan Saluang Belum Terhadap Bakteri Staphylococcus aureus: Inhibitory test of Saluang Belum Stem Ethanol Extract on staphylococcus aureus - Qamariah, Nurul; Handayani, Rezqi; Friskila, Andika (Jurnal Surya Medika (JSM), 2018)
One of the medicinal plants used by the people of Katingan Regency, Central Kalimantan Province is the Saluang Belum stem, which empirically used as an aphrodisiac to increase stamina, sexual and fertility of male, and as an antioxidant. The purpose of this study was to find out the inhibition and to know which concentration of ethanol extract of Saluang Belum stem which had been able to inhibit the growth of Staphylococcus aureus bacteria. This research uses an experimental method with a laboratory approach. The results of the inhibitory zone of ethanol extract of Saluang Belum stem at a concentration of 0.5% was 26.7 ± 2.76 mm, at a concentration of 1% was 21.6 ± 2.20 mm, at a concentration of 5% was 20.5 ± 0, 90 mm, at 10% concentration was 21.2 ± 1.11 mm, at 15% concentration was 23.2 ± 0.23 mm, and at 20% concentration was 25.5 ± 0.36 mm. Conclusions from this study were that the MIC (Minimum Inhibitory Concentration) obtained at 0.5% concentration of ethanol extract Batang Saluang Belum was able to inhibit the Staphylococcus aureus bacteria.